Corporate strategy of Bangko Sentral ng Pilipinas - Turaray, Eleanor S. (Animo Repository, 1999)
When gold was used as a standard in the past, the value of central bank notes was expressed in terms of its gold metal content. Central banks attempted to maintain gold at stated levels over time. The gradual replacement of the gold standard with pure fiat standards in the twentieth century has, in time changed the objective of central banks policies into maintaining price stability. Central banks worldwide are responsible for policies to maintain financial stability in their respective countries. Operations in world economies can be traced based on their macroeconomic and microeconomic functions. The macroeconomic function is to preserve the value of the currency, that is, maintain price stability and the microeconomic function, to maintain stability in the banking system. If price stability accelerates economic growth, then the central bank promotes economic development by delivering price stability. There are two prerequisites that must be satisfied to enable the central bank to conduct effective monetary policy (a) a safe and efficient payment system and (b) financial stability. Good monetary policy, financial stability and efficient payment systems all contribute to economic development. As the provider of the ultimate means of settlement, central banks are essential in maintaining the stability of the respective financial system. The Bangko Sentral ng Pilipinas is the central monetary authority of the Philippines. It plays a vital function in the country's financial system. It does not only supervise the banking system and other financial institutions but also direct the country to development. It is through BSP that government attain economic and financial goals and objectives. Both BSP and the government are instrumental in the attainment of economic and financial stability. The BSP can be independent within its structure but it cannot be independent of government per se. The primary objective of the Bangko Sentral ng Pilipinas is to to maintain price stability conducive to a balanced and sustainable growth of the economy. To attain this, the BSP endeavors to control any expansion or contraction in monetary aggregates. Price stability is secured when the peso holds its value in terms of purchasing power, i.e., what it can buy over the whole range of a nations' goods and services. To better understand the functions and responsibilities of BSP and determine the reasons for such behavior, it is important to get an overview of the Philippine financial system and the current macroeconomic conditions in order to analyze the strategies of BSP and how it has performed its functions. In addition, a brief discussion on the Asian financial crisis will be presented to give a background of its origin and how the BSP reacted and finally being able to avert its worst effects. The monetarist theory of economics will be used as a general framework to assess and evaluate the major strategic monetary policies of BSP. In addition, a corporate strategy on electronic payment systems will also be presented as BSP's move to enhance its function as financial advisor of the national government towards economic development. The strategic alignment model of dynamic panning framework will serve as basis of analysis to scrutinize the development, implementation and long-term benefits of the strategy. Full implementation of the electronic funds transfer instruction system is yet to be accomplished in year 2000 with the foremost objective that of a fast and efficient system of moving funds to the national government for better cash management policies. Effects of the new technology should not be seen as just mere improvement of operations but rather as a precedent of future developments in the financial (banking) industry sector as BSP spearheads the country into economic growth and development.